2021
DOI: 10.1186/s12937-021-00728-y
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and lifestyle factors modifies the association between snack foods intake and incidence of metabolic syndrome

Abstract: Background Intake of snack foods has been previously associated with an elevated risk of chronic disease; however, studies on snack foods and metabolic syndrome (MetS) while considering the modifying effect of socioeconomic status (SES) and lifestyle factors on this association are lacking. We aimed to investigate the association between snack foods intake and the MetS risk, and the mediatory effects of SES and lifestyle factors on the forenamed association among adults who participated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the types of snacks consumed by young adults are usually characterized by high amounts of fat, sugar, and total calories, and are considered unhealthy eating habits that might contribute to weight gain [ 18 , 19 ]. Prior evidence suggests that chocolates/candies, cookies, biscuits, donuts, potato chips, and nuts are among the most common types of snacks consumed by university students [ 49 , 61 , 62 , 65 ]. Remarkably, our results also showed that almost 40% of university students consumed fruits and vegetables as snacks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the types of snacks consumed by young adults are usually characterized by high amounts of fat, sugar, and total calories, and are considered unhealthy eating habits that might contribute to weight gain [ 18 , 19 ]. Prior evidence suggests that chocolates/candies, cookies, biscuits, donuts, potato chips, and nuts are among the most common types of snacks consumed by university students [ 49 , 61 , 62 , 65 ]. Remarkably, our results also showed that almost 40% of university students consumed fruits and vegetables as snacks.…”
Section: Discussionmentioning
confidence: 99%
“…Food items that are high in fat, sugar, and total calories, such as chocolate and potato chips, are commonly consumed as snacks [ 6 ]. Prior research has shown that snack intake may be associated with obesity and metabolic syndrome [ 7 9 ]. Other studies have reported contradictory findings [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the previous studies support this hypothesis. Previous studies have shown that the consumption of candy and chocolate increases the risk of MetS by more than 30% [ 48 ]. In addition, university students who consumed snacks had a high energy intake and a 15.36 times higher risk of having two or more MetS risk factors [ 49 ].…”
Section: Discussionmentioning
confidence: 99%